Progression to diabetes : 5 year follow-up of the Northland Diabetes Screening and Cardiovascular risk assessment pilot : a thesis presented to fulfil requirements for the degree of Master of Public Health at Massey University, Wellington, New Zealand - White, Bronwyn Kaye (Massey University, 2014)
Aim: The primary aim was to determine the effect the Northland Diabetes Screening and Cardiovascular risk assessment pilot had on the progression from a normal glucose test (NGT) at baseline to diabetes. Method: Patients from a single practice (Maori = 1509, Non-Maori = 619) who were invited onto the pilot with NGT at baseline were retrospectively followed up for 7 years. Results for Pilot (PG) (Maori = 336, Non-Maori 255) and Non-Pilot (NPG) groups (Maori = 537, Non-Maori = 204) were compared on progression to diabetes, impaired glucose tolerance (IGT), all-cause mortality. Results for Maori: There were 10 incidence cases of diabetes, 20 IGT and 18 deaths from any-cause during a median duration of follow-up of 6.4 years in the PG compared with 22 incidence cases of diabetes, 23 IGT and 30 deaths from any-cause in the NPG followed for a median duration of 4.3 years. Participation in the pilot was associated with a statistically significant protective effect on progression to diabetes (Age-adjusted rate ratio 0.44(95% CI 0.2156, 0.912) and all-cause mortality (Age-adjusted rate ratio 0.49 (95% CI 0.2771, 0.8626). Results for Non-Maori: There were 12 incidence cases of diabetes, 13 IGT diagnoses and 19 deaths from any-cause during a median duration of follow-up of 6.2 years in the PG compared with 9/204 diabetes incidence cases, 11 IGT and 13 deaths from any-cause in the NPG followed for a median duration of 4.7 years. There was no statistically significant association with participation in the pilot on progression to diabetes, IGT or all-cause mortality. Conclusion: The protective effect for Maori patients in the pilot on progression to diabetes was either because they had inherently lower risk than the non-pilot group or potentially because their baseline results were interpreted in the context of their CVD risk. The effectiveness of CVDRA programmes on reducing incidence diabetes should be formally assessed. Research focusing on risk reduction for Maori aged 35-49 years is recommended.
Keywords: Medical screening; Diabetes; Cardiovascular disease; Cardiovascular system diseases; Coronary heart disease; Maori; Epidemiology; Risk assessment; Medical examinations; Northland; New Zealand